The Association Between ICD Interventions and Mortality is Independent of their Modality: Clinical Implications. (3rd September 2014) - BENCARDINO, GIANLUIGI; DI MONACO, ANTONIO; RIO, TERESA; FRONTERA, ANTONIO; SANTANGELI, PASQUALE; LEO, MILENA; PELARGONIO, GEMMA; PERNA, FRANCESCO; NARDUCCI, MARIA LUCIA; GABRIELLI, FRANCESCA; LANZA, GAETANO ANTONIO; BELLOCCI, FULVIO; et al.
ICD Interventions and Mortality Background Patients with severe structural heart disease have increased mortality after implantable cardioverter‐defibrillator (ICD) shocks. Whether this is limited to ICD shock therapy only or extends also to no‐shock therapies, such as antitachycardia pacing (ATP), is unclear. We investigated the impact of different ICD therapies on long‐term mortality. Methods We enrolled 573 patients who underwent ICD implantation at our institution from 2004 to 2011. The population was divided into 3 groups: no device interventions (group 1), ATP interventions (group 2), and shock interventions (group 3). The endpoint was the all‐cause mortality. Results Over a follow‐up period of 48 months (range 1–110), 447 (78%) had no device interventions, 71 (12%) had ATP therapy only, and 55 (10%) had at least one shock intervention. All‐cause mortality occurred in 94 patients in group 1 (21%), 23 patients (43%) in group 2, and 21 patients (38%) in group 3. At multivariable Cox regression analysis, ATP intervention (HR: 1.8; 95% CI 1.1–3; P < 0.001), shock intervention (HR: 1.39; 95% CI 1.09–1.77; P = 0.008), age (HR: 1.05; 95% CI 1.02–1.07; P < 0.001), and LVEF (HR: 0.95; 95% CI 0.93–0.98; P = 0.001) were predictors of all‐cause mortality. No significant difference in mortality was found between group 2 and 3. Conclusion Patients with ICDs who receive appropriate interventions are at increased risk of mortality. Such risk is not dependent on different types of ICD therapy, such as shocks or ATP. Our data suggest that sustained ventricular arrhythmias per se have a negative impact on prognosis rather than modality of ICD therapy.